Basic Potential of Carbon Nanotubes in Tissue Engineering Applications. (11th April 2012) - Haniu, Hisao; Saito, Naoto; Matsuda, Yoshikazu; Tsukahara, Tamotsu; Usui, Yuki; Narita, Nobuyo; Hara, Kazuo; Aoki, Kaoru; Shimizu, Masayuki; Ogihara, Nobuhide; Takanashi, Seiji; Okamoto, Masanori; et al.
Abstract : Carbon nanotubes (CNTs) are attracting interest in various fields of science because they possess a high surface area-to-volume ratio and excellent electronic, mechanical, and thermal properties. Various medical applications of CNTs are expected, and the properties of CNTs have been greatly improved for use in biomaterials. However, the safety of CNTs remains unclear, which impedes their medical application. Our group is evaluating the biological responses of multiwall CNTs (MWCNTs) in vivo and in vitro for the promotion of tissue regeneration as safe scaffold materials. We recently showed that intracellular accumulation is important for the cytotoxicity of CNTs, and we reported the active physiological functions CNTs in cells. In this review, we describe the effects of CNTs in vivo and in vitro observed by our group from the standpoint of tissue engineering, and we introduce the findings of other research groups.